NLR genes: infection, inflammation and vaccines - Ting, Jenny (Henry Stewart Talks, 2009)
Pattern recognition/sensing molecules, Identification of the NBD-LRR (NLR) family, Autoimmune and Infectious Diseases associated with NLR polymorphisms/mutations, Functions of NLR proteins, The multiple functions of NLRP3, The NLR-based inflammasomes, Shigella flexneri, NLRP3 and necrosis, New functions of NLRP3, NLRX1, The indirect recognition of PAM by NLR
Archived at 2021/02/25